MUSLIM TOURIST SATISFACTION OF HALAL TOURISM IN LOMBOK - Rahmiati, Filda; Othman, Norfaridatul Akmaliah; Sunanti, Meilisa Audina Putri (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2018)
The rising of Muslim population around the world creates the increasing demand for tourism in accordance with Islamic rules called as Halal Tourism. This study examined Lombok islands which have won an International Halal Destination Award in 2016. This study investigates Destination Image, Perceived Value and Islamic Value impact on Muslim Tourist Satisfaction of Halal Tourism in Lombok. This research used 110 respondents using non-probability sampling with convenience sampling and a survey through questionnaires. Data analysis procedures used in this study is Multiple Linear Regression. Based on Multiple Linear Regression, a result of Destination Image, Perceived Value, and Islamic Value were found to have the positive and significant impact on Muslim Tourist Satisfaction partially and simultaneously with R2 of 0.775. It indicates that 77.5 persen of the variance in Muslim Tourist Satisfaction in Lombok influenced by Destination Image, Perceived Value, and Islamic Value. The recommendation is given to future study are used this three variables in other locations of halal tourism in Indonesia, therefore, it will create a sustainable halal tourism of Indonesia which create a competitive advantage in attracting tourist to visit Indonesia for Halal tourism purposes